Roles of Retinoids and Retinoic Acid Receptors in the Regulation of Hematopoietic Stem Cell Self-Renewal and Differentiation - Louise E. Purton (PPAR Research)
Multipotent hematopoietic stem cells (HSCs) sustain blood cell production throughout an individual's lifespan through complex processes ultimately leading to fates of self-renewal, differentiation or cell death decisions. A fine balance between these decisions in vivo allows for the size of the HSC pool to be maintained. While many key factors involved in regulating HSC/progenitor cell differentiation and cell death are known, the critical regulators of HSC self-renewal are largely unknown. In recent years, however, a number of studies describing methods of increasing or decreasing the numbers of HSCs in a given population have emerged. Of major interest here are the emerging roles of retinoids in the regulation of HSCs.